Aldosterone-independent regulation of the epithelial Na(+) channel (ENaC) by vasopressin in adrenalectomized mice - Mironova, Elena (National Academy of Sciences, 2012)
The epithelial Na(+) channel (ENaC) in the aldosterone-sensitive distal nephron (ASDN) is under negative-feedback regulation by the renin–angiotensin–aldosterone system in protection of sodium balance and blood pressure. We test here whether aldosterone is necessary and sufficient for ENaC expression and activity in the ASDN. Surprisingly, ENaC expression and activity are robust in adrenalectomized (Adx) mice. Exogenous mineralocorticoid increases ENaC activity equally well in control and Adx mice. Plasma [AVP] is significantly elevated in Adx vs. control mice. Vasopressin (AVP) stimulates ENaC. Inhibition of the V(2) AVP receptor represses ENaC activity in Adx mice. The absence of aldosterone combined with elevated AVP release compromises normal feedback regulation of ENaC in Adx mice in response to changes in sodium intake. These results demonstrate that aldosterone is sufficient but not necessary for ENaC activity in the ASDN. Aldosterone-independent stimulation by AVP shifts the role of ENaC in the ASDN from protecting Na(+) balance to promoting water reabsorption. This stimulation of ENaC likely contributes to the hyponatremia of adrenal insufficiency.